Amygdalin reduces lipopolysaccharide-induced chronic liver injury in rats by down-regulating PI3K/AKT, JAK2/STAT3 and NF-κB signalling pathways. Issue 1 (4th December 2019) - Yang, Yang; Zhao, Jie; Song, Xiaoqin; Li, Lifeng; Li, Fuqin; Shang, Jia; Wang, Wei-Wei
Abstract: This study was aimed to evaluate the anti-inflammatory potential of AG on lipopolysaccharide (LPS) -induced liver injury and investigate the underlying mechanism. Administration of LPSs in the rat produced rat liver injury model which was ascertained at histological and molecular levels. Those models were treated with a range of doses of LPSs (0.5, 1.0 and 1.5 mg/kg body weight), followed by measurement physical parameter and function of the liver. Within the max treatment doses, no toxicity was shown but protective effects of AG were evidenced by regulation of physical parameters and functions of the liver. Interestingly, nuclear factor kappa B (NF-κB) levels and inflammatory factors were down-regulated by AG. Furthermore, the histopathological analysis demonstrated that AG promoted recovery from dysfunction of liver tissue in the rats, which was further confirmed by observing expression changes of inflammation-associated proteins. Particularly, alteration in the PI3K/AKT and JAK2/STAT3 signalling pathway protein expression were regulated by AG in a dose-dependent manner, indicating the mechanism underlying the relief effect of AG in liver injury. Our study demonstrated the potential of AG in the management of complications related to liver injury.